HEALTH STATE OF NOVOSIBIRSK SCHOOLCHILDREN ACCORDING TO PREVENTIVE EXAMINATIONS IN DYNAMICS - Елкина, Татьяна Николаевна; Лиханова, Маргарита Геннадьевна; Пирожкова, Наталья Игоревна; Суровикина, Екатерина Александровна; Татаренко, Юлия Анатольевна (Mother and Baby in Kuzbass, 2024)
The aim of the research – to study the health status of school-age children based on the results of medical examinations, to analyze the structure of school-related diseases. Materials and methods. We analyzed 283 and 306 cards of preventive medical examinations of a minor (Registration form N 030-PO/u-17) in 2016 and 2023, respectively. A retrospective comparative assessment of the ratio of health groups in school-age children and the prevalence of school-related pathology in 2016 and 2023 was carried out. The processing of the material was carried out using a package of modern statistical programs. Results. Analysis of the distribution of schoolchildren by health group showed a predominance of health group II in all age groups. The dynamics of the number of adolescents with health group II was noted. Teenagers with group III take second place in both 2016 and 2023, with an increase in this group by 2023. Among schoolchildren aged 7-8 and 10-11 years, there are more children with health groups I and II. It has been shown that the most common school-related diseases in school-age children are still diseases of the musculoskeletal system, the eye and its appendages, the gastrointestinal tract and the nervous system. Conclusion. Among schoolchildren, regardless of age, both in 2016 and in 2023, the leading place is occupied by health group II. The rate of absolutely healthy children (health group I) remains low, with a tendency to a significant reduction by adolescence. The results of our study indicate a high prevalence of school-related diseases among children and adolescents. The number of healthy children who do not have manifestations of school-related diseases is reduced during their schooling. The identified pathology in younger schoolchildren has a negative upward trend, which leads to the formation of pathological conditions by adolescence.